Comparative Study on Civic Education - Zaleskienė, Irena (Acta Paedagogica Vilnensia, 2001)
An Overview of the IEA (International Association for Evaluation of Educational Achievement) Civic Education Study (CivEd) is developed by the Lithuanian National Research Coordinator. Lithuania is one of the 29 countries participating in this International Study. The author presents the main ideas, goals of the Study, the structure of the Test Instruments, School Sampling, etc. The needed materials (The summaries of Core International Framing Questions; Review of Literature; National Case Study Chapter: “National Identity and Education for Democracy" were developed during the phase l. They are included in the International publication: J. Torney Purta, J. Schwille and J. A. Arnadeo. Civic Education across Countries: Twenty-Four National Case Studies from IEA Educational Project. Amsterdam: International Association for the Evaluation of Educational Achievements, 1998. The testing of 14-years old students took place in 1999. The full data will be available for comparison only in 2001, thus author presents just some ideas about civil maturity of the Lithuanian adolescence.